Reference and information services an introduction - Cassell, Kay Ann; Hiremath, Uma (Chicago ALA Neal-Schuman, 2023)
"The fifth edition of Reference and Information Services: An Introduction is consciously aimed at arming the reference librarian with the skills, expertise, and mindset needed to keep up with changing resources and best practices"--
Part I. Fundamental concepts -- Introduction to reference and information services -- Determining the question : in-person, telephone, and virtual reference interviews -- Finding the answer : basic search techniques -- Part II. Introduction to major reference sources -- Answering questions about books, magazines, newspapers, libraries and publishing, and bibliographic networks : bibliographic resources -- Answering questions about anything and everything--encyclopedias -- Answering questions that require handy facts--ready reference sources -- Answering questions about words--dictionaries, concordances, and manuals -- Answering questions about current events, issues and research topics--databases (and indexes) -- Answering questions about law and business--special guidelines and sources -- Answering questions about health--special guidelines and sources / Emily Vardell -- Answering questions about geography, countries, and travel--atlases, gazetteers, maps, geographic information systems, and travel guides -- Answering questions about the lives of people--biographical information sources -- Answering questions about government and related issues--government information sources -- Part III. When and how to use the internet as a reference tool -- Readers' advisory services / Maria Fesz and Cindy Orr -- Reference services for children and young adults / Melissa Gross -- Information literacy in the reference department -- Part IV. Developing and managing reference collections and services -- Selecting and evaluating reference material -- Managing reference departments -- Assessing and improving reference services -- Ethics in reference / Diana Floegel -- Reference 2.0 -- The future of information services -- Appendix A. RUSA outstanding reference sources 2012-2022 -- Appendix B. RUSA definition of reference.
Includes bibliographical references and indexes.
Keywords: Electronic reference services (Libraries); Reference services (Libraries); Electronic reference sources -- Directories; Reference books -- Bibliography